The J.I. Packer classic collection : daily readings for your spiritual journey - Packer, J. I. (James Innell); Womack, Thomas (Colorado Springs, CO : Navpress, 2010)
Presents daily devotions that feature excerpts from the author's writings and teachings, including "Praying the Lord's Prayer" and "Evangelism and the Sovereignty of God."
Includes bibliographical references and index.
Keywords: Devotional calendars; Christian life -- Meditations